2015
DOI: 10.1186/s40064-015-1241-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of cage culture in Lake Victoria: the case of Shirati Bay-Sota, Tanzania

Abstract: The experimental cage culture was conducted at Shirati bay, Lake Victoria from February to August 2013, to investigate the impacts of the small scale cage culture on the environment. Three locations along the cages, at the intermediate and one in the offshore (control) were sampled for water quality parameters, phytoplankton and macro invertebrates. A notable increase in nutrient concentration was observed after the set of cages among the stations. However DO, pH, and water transparency showed no major changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 15 publications
2
31
1
1
Order By: Relevance
“…In Napoleon Gulf (Uganda), Egessa et al (2018) observed organic matter and nutrient enrichment in the sediment due to cage fish farming. In Shirati Bay (Tanzania), an increase in nutrient concentrations was observed after cage farming establishment (Kashindye et al 2015), while in Kenya, Njiru et al, (2018) reported increasing eutrophication in shallow areas due to aquaculture waste feeds. These areas are only small portions of LV where caged fish farming has occurred, but farming has begun to spread among the various B&Gs of the lake.…”
Section: Other Processes Involved In the Increasing Occurrence Of Cyamentioning
confidence: 99%
“…In Napoleon Gulf (Uganda), Egessa et al (2018) observed organic matter and nutrient enrichment in the sediment due to cage fish farming. In Shirati Bay (Tanzania), an increase in nutrient concentrations was observed after cage farming establishment (Kashindye et al 2015), while in Kenya, Njiru et al, (2018) reported increasing eutrophication in shallow areas due to aquaculture waste feeds. These areas are only small portions of LV where caged fish farming has occurred, but farming has begun to spread among the various B&Gs of the lake.…”
Section: Other Processes Involved In the Increasing Occurrence Of Cyamentioning
confidence: 99%
“…First studies on impact of fish cage operations on surrounding water environment in L. Malawi [115,116] were minimal despite substantial discharges from the cages, due to dispersion by water currents and aggregation of wild fish species feeding on the wastes. Experimental studies on cage culture from Uganda and Tanzanian side of L. Victoria found no consistent environmental changes using water quality parameters, phytoplankton and macro-invertebrates [117,118]. Effect of nutrient discharge on DO was not pronounced.…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…Enhancing nutrient status as illustrated by the eutrophication problems in L. Victoria can lead to a number of undesirable effects (Hecky, Mugidde, Ramlal, Talbot & Kling, 2010). Current development of in situ fish cage aquaculture requires further monitoring and environmental risk assessment (Aura et al, 2018;Kashindye et al, 2015).…”
Section: The Way Forward and Prognosis For Sustainabilitymentioning
confidence: 99%